2007
DOI: 10.1086/519777
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Age Constraints and Metamorphic History of the Talladega Belt: New Evidence for Timing of Arc Magmatism and Terrane Emplacement along the Southern Laurentian Margin

Abstract: Talladega belt, southernmost Appalachians, provide insight into the timing and nature of pre-Alleghanian tectonism in this region. Low-grade metasedimentary rocks of the Talladega belt represent the outermost preserved portions of the southern Laurentian margin, thus recording the earliest orogenic events that affected the margin, in addition to later overprinting events. These rocks are structurally overlain by the Hillabee Greenstone metavolcanic sequence, from which metadacite yields an age of ‫4ע074‬ Ma (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 49 publications
4
35
1
Order By: Relevance
“…Steltenpohl et al (2004) report a 354 ± 140 Ma lower intercept U-Pb age on detrital zircons from the Hollis Quartzite, which is consistent with fossil evidence for post-early Mississippian metamorphism in the nearby Talladega slate belt ( Fig. 2; Gastaldo et al, 1993;McClellan et al, 2007) and a <337 Ma 40 Ar/ 39 Ar date suggested for hornblende from the Pine Mountain window (Steltenpohl and Kunk, 1993). Nonetheless, the T-t path corroborates the suggestion of Steltenpohl and Kunk (1993) that the Pine Mountain terrane had occupied middle-crustal levels during the Alleghanian event and that it was joined with the Uchee terrane either prior to or during this event before being uplifted and cooled as a somewhat coherent block.…”
Section: Hollis Quartzite Pine Mountain Terranesupporting
confidence: 53%
“…Steltenpohl et al (2004) report a 354 ± 140 Ma lower intercept U-Pb age on detrital zircons from the Hollis Quartzite, which is consistent with fossil evidence for post-early Mississippian metamorphism in the nearby Talladega slate belt ( Fig. 2; Gastaldo et al, 1993;McClellan et al, 2007) and a <337 Ma 40 Ar/ 39 Ar date suggested for hornblende from the Pine Mountain window (Steltenpohl and Kunk, 1993). Nonetheless, the T-t path corroborates the suggestion of Steltenpohl and Kunk (1993) that the Pine Mountain terrane had occupied middle-crustal levels during the Alleghanian event and that it was joined with the Uchee terrane either prior to or during this event before being uplifted and cooled as a somewhat coherent block.…”
Section: Hollis Quartzite Pine Mountain Terranesupporting
confidence: 53%
“…Based on decades of surface geological studies, correlations of buried rocks with otherwise known features outside of Alabama, and drill-core data, the crust underlying Alabama is recognized as belonging to three fundamental types: 1) Laurentian, 2) peri-Gondwanan, and 3) Gondwanan (Neathery and Thomas, 1975;Hatcher, 1978Hatcher, , 1987Hatcher, , 2010Tull, 1982;Chowns and Williams, 1983;Horton et al, 1984;Tull, 1978Tull, , 1980Tull, , 1982Tull, , 1984Guthrie and Raymond, 1992;Drummond et al, 1994Drummond et al, , 1997Steltenpohl, 2005;McClellan et al, 2005McClellan et al, , 2007Steltenpohl et al, 2008Steltenpohl et al, , 2010a. Our results from comparing regional geophysical data with the surface and subsurface geology indicate clear demarcation of Laurentian crust in roughly the northwestern half of Alabama, and periGondwanan or Gondwanan crust underlying the southeastern quarter.…”
Section: Discussion and Directions For Future Studiesmentioning
confidence: 99%
“…Farther northeast into Georgia most geologic maps depict the fault to be the Allatoona fault (Hurst, 1973;Tull, 1978;Hatcher et al, 1990;Tull and Holm, 2005). The Goodwater-Enitachopco/Allatoona fault has been interpreted as a southeast-dipping reverse (thrust) fault (Neathery and Tull, 1975;Pickering, 1976;Tull, 1978Tull, , 1984Costello, 1980, 1982;Crawford and Cressler, 1982;McConnell and Abrams, 1984;Osborne et al, 1988;McClellan et al, 2005;Tull and Holm, 2005). , on the other hand, interpreted the Goodwater-Enitachopco to be a normal fault, reasoning that a thrust fault cutting the basal eastern Blue Ridge thrust (i.e., the Hollins line) should emplace Talladega slate belt rocks in the hanging wall.…”
Section: Discussion and Directions For Future Studiesmentioning
confidence: 99%
See 2 more Smart Citations